Incidence of catheter-related bloodstream infection (CRBSI) in immunosuppressed hosts post solid organ transplant (SOT): a single center experience - El Mouhayyar, Christopher; Al Jurdi, Ayman; Safa, Kassem (Frontiers in Transplantation, 2025)
IntroductionCatheter-related bloodstream infections (CRBSI) incidence is well-studied in general hemodialysis patients. There is a lack of data on CRBSI rates specifically in solid organ transplant (SOT) recipients requiring hemodialysis. This study aims to investigate CRBSI incidence in this population at a single center.MethodsThis retrospective, single-center cohort study at Massachusetts General Hospital (MGH) investigated CRBSI incidence in non-kidney SOT (i.e., heart, lung, liver) who required hemodialysis via a tunneled dialysis catheter (TDC). Data was collected from January 2016 to October 2024, with patients followed for up to two years post-transplant or until death/end of study.Results42 individuals met the study's inclusion criteria. The mean age of this cohort was 57 years, 50% were male, and 81% were White. The group consisted of 17 liver transplant recipients (40.5%), 13 heart transplant recipients (31.0%), and 12 lung transplant recipients (28.6%). Among the 12 lung transplant recipients, 8 received basiliximab induction, and 4 received no antibody induction therapy. 97% of the patients received mycophenolate mofetil, tacrolimus, and prednisone, while 3% received steroid-free maintenance. The median follow-up was 51.5 days (interquartile range 16–233). During this period, six individuals developed CRBSI, resulting in an incidence rate of 0.86 infections per 1,000 catheter-days. No deaths were attributed to CRBSI.ConclusionsOur findings suggest that intense immunosuppression in the setting of SOT is not associated with an increased risk of CRBSI in patients with renal failure utilizing TDC especially when a consistent and standardized protocol for the access and care of these catheters is utilized.